Customer Satisfaction Analysis Using Quality Function Deployment: A Case Study on Malaysian Domestic Airlines - Mohd Salleh, Rohayu (Enhanced Knowledge in Sciences and Technology, 2022)
In this age of globalization, airline service quality has become a popular issue in the global air transportation industry. Due to the intensely competitive market situation, the airline company requires to focus on the passenger’s experience and satisfaction. This study attempts to conduct a customer satisfaction analysis by using quality function deployment as a case study on Malaysian domestic airlines. The data of three Malaysian domestic airlines; AirAsia (217 observations), Malaysia Airlines (215 observations) and Malindo Air (242 observations) were collected from the Skytrax website from June 2013 to January 2020. The word “Service” is found to be the most frequent word that appears in the passengers’ review on Malaysian domestic airlines through the text mining analysis. Quality function deployment was adopted to systematically determine the priority in customer requirements through the development of house of quality. Based on the relative importance of customer requirements, value for money had been determined to be the priority. The house of quality formulates a service planning matrix beneficial to Malaysian domestic airlines. It provides a guideline to focus on, i.e. the specification improvement on their service performance to enhance customer satisfaction.